Exergy analysis of tea drying in a continuous vibro-fluidised bed dryer - Ozturk, Merve; Dincer, Ibrahim (INDERSCIENCE ENTERPRISES LTD, 2019)
In the current study, a comprehensive thermodynamic investigation through energy and exergy analyses is performed to study and assess the performance of a three-stage tea drying system which has vibro-fluid bed dryer. Also, energy and exergy efficiencies are, in this regard, investigated with the thermodynamic data obtained from the literature. The parametric studies are carried out to investigate the effects of varying the state properties and operating conditions on the performance of the drying system. The overall energy and exergy efficiencies of the system are found as 42% and 7.2%, respectively. The main reason for the low exergy efficiency is the high exergy destruction rate for the components of the system. The total exergy destruction ratio of drying chambers is calculated as 58% of overall exergy destruction rate of the system.
Keywords: drying; tea; energy; exergy; efficiency; vibro-fluid bed dryer; BLACK TEA; THERMODYNAMIC ANALYSIS; PERFORMANCE ANALYSIS; HEAT-PUMP; Thermodynamics; Energy & Fuels